ANALYSIS OF FEMALE LABOR RATES AT PT. NOBLE BHAKTI KAHURIPAN (MBK) RIVER LAUR SUB-DISTRICT KETAPANG DISTRICT - Wilna .; Abdul Hamid A. Yusra; Rakhmad Hidayat (Jurnal Sains Pertanian Equator, 2019)
This study aims to analyze the wage rate of female workers in PT. Mulia Bhakti Kahuripan which is an oil palm company. The analysis used in this study is multiple linear regression analysis. This study uses 50 respondents who are status as freelance daily employees (PHL). The results showed that the lowest SFM / female worker income was Rp.672,000.00 / month and the highest income was Rp. 864,000.00. PHL working hours / female workers with the lowest working hours of 168 hours / month and the highest 216 hours / month. the lowest is 25 years old and is the highest age of 50 years. The largest frequency of education is as many as 22 respondents or 44% determined by the category of junior high school graduation. The smallest respondents were 12 or 24% of high school graduates. This shows that SFM / female workers are mostly secondary education (SMP). Keywords :working hours , education, type of work, number of families